The Effect Cucurbita Moschata Pudding on Weight Gain in Malnourished Toddlers In Indonesia - Henny Sulistyawati; Nining Mustika Ningrum; Tri Purwanti utomo (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
The food is given to the undernourished according to WHO standards is made from oil, sugar, milk, water, and flour. Fulfillment of Supplemental Foods can be made by yourself with a composition that contains energy and protein intake from ingredients that are easily obtained by the community at an affordable cost. Yellow pumpkin (Cucurbita moschata), one of the local functional food ingredients, is proven to have many health benefits. The type of research used was a quasi-experimental design non-equivalent control group. This study analyzed the effect of giving cucurbita moschata pudding on increasing the weight of undernourished toddlers. experiment, the results of observations are then controlled or compared with the results of observations in the control group that did not receive the program or intervention. Data were processed using the SPSS Version 21 program. The results using the Paired Sample T-Test showed a significant number between the intervention group and the control group with a significant value (2-tailed) p=0.000 <0.05. There is an effect of giving cucurbita moschata pudding on increasing the weight of malnourished babies. The results of the research can add to the knowledge and insight of parents to give Curbita Moschata Pudding as baby nutrition and to provide proper diet and parenting patterns for babies so that babies feel comfortable when eating.